Non-human Primate Papillomaviruses Share Similar Evolutionary Histories and Niche Adaptation as the Human Counterparts - Chen, Zigui; Long, Teng; Wong, Po Yee; Ho, Wendy C. S.; Burk, Robert D.; Chan, Paul K. S. (Frontiers in Microbiology, 2019)
Given high genetic diversity of papillomaviruses (PV) and complex scenario of virus-host interaction, the genetic basis underlying the mechanisms of HPV carcinogenicity is not well understood. In an effort to evaluate the origin and evolution of PV pathogenicity, we collected paired oral, perianal and genital swabs from a wild macaque population. Of the 117 surveyed macaques, 88 (75.2%) were positive for PV DNA in one or more sites, mostly common from genital swabs, followed by oral and perianal sites. All putative macaque PV types phylogenetically clustered into the genera Alpha-, Beta-, and Gammapapillomavirus, with a strong phylogeny-tropism association as observed in HPVs. Using a Bayesian Markov Chain Monte Carlo framework, we demonstrated ancient intra-host divergence of primate PVs in which multiple ancestors had split and adapted to specific host ecosystems at least 41 million years ago, prior to the speciation events of primate host species. Following subsequent divergence and niche adaptation, distinct but phylogenetically related PV types were transmitted to similar host ecosystems by closely related host animals when host speciation occurred, which may explain in part the origin of carcinogenicity of HPV type 16 (HPV16) and Macaca fascicularis PV type 3 (MfPV3) that evolved from a most recent common ancestor containing the determinants for cervicovaginal colonization and cervical cancer. The findings identifying evolutionary and biological relatedness between human and non-human primate PVs lay a genetic foundation for research on parasite-host interactions and carcinogenic outcomes, which will prove useful in further study of viral pathogenesis and host specificity.